Challenges and Opportunities of Big Data for Managing the E-Governance - Md. Mahbobor Rahaman; Afruza Haque; Md.Foysal Hasan (Garuda Prestasi Nusantara Consulting, 2021)
In the age of digitalization, big data is the most applicable and critical factors for making and running a e-government. Big data analytics is using for solving the most complex existing and future problems which can be arisen at any time of digital governance. The study will focus on the opportunities of big data for managing the e-government by better utilization of ICT resource and e-government services. The study also deals with the challenges of big data management in managing the data privacy, security of risk, data analysis tools, e-government management structure, big data frameworks, data recovery and disaster management systems. The study finds out the way, how can e-government service be provided with the help of stakeholder and performance-oriented e-government structure. A model will be introduced to describe the current state of digital government in Bangladesh and compared with the other standards of digital government framework. The model of big data analytics will also be describing the challenges and opportunities of good e-governance of Bangladesh. The study will finally find out the way of managing the big data analytics in handling the e-governance. The study will be concluded with the key findings and scope for the future research in big data analytics and public administration.